Taxonomic and ecological study of Chironominae larvae (Chironomidae : Diptera) and Mollusca in the junction of Balloran and Seryscia rivers, north of Latakia city (Journal of Hama University, 2020)
Samples of Chironominae larvae and Mollusks were collected from Balloran and Seryscia rivers  junction station since December 2017 till May 2019. Three genres belong to Chironominae (Chironomus, Apedilum, Microtendipies), five species belong to chironomus: Chironomus plumosus, Ch. riparious, Ch. stigmaterus, Ch. austini Ch. dorsalis and Apedilum elachistus belong to the second were identified. The last two genres and the last species were recorded for the first time in Syria. Also 5 species of Mollusca were identified for the first time in this station ( Melanopsis praemorsa, Physa acuta, Physa phontinalis, Planorbis. umbilicatus, Sphaerum  lacustre). Physical and chemical properties of water were studied and the results were diagrammed. Some of  biocenose characteristics were studied.